DEVELOPMENT OF A METHODOLOGY FOR SELECTING THE LOCATION OF TRANSPORT INTERCHANGE HUBS IN CITIES (Web of Teachers: Inderscience Research, 2026)
In major cities around the world, the leading issues are the correct selection of the location of transport interchanges, determining economic and social efficiency, directing passengers to public transport through the effective organization of coordinated movement of transport modes, and minimizing the total time spent by passengers to reach their destinations while providing reliable transport service. Various mechanisms have been developed by transport scientists around the world to correctly select the location of transport interchanges. As a result of research conducted by world scientists on the correct location of transport interchanges, it was determined that the time spent by passengers on the journey is one of the main criteria, and work was carried out to minimize the total travel time, costs and emissions of environmentally harmful gases from transport vehicles. An algorithm for optimizing the location of transport interchanges (Transport Interchanges) was developed taking into account the initialization of the main parameters, determination of the objective function, verification of boundary conditions, solution of the optimization problem and determination of the results. This article is devoted to the development of a methodology for selecting the location of transport interchanges in cities.